Rancang Bangun Sistem Manajemen Power Supply Portable Pada Node Early Warning System Mitigasi Bencana Kebakaran Lahan Gambut - Muammar, Taufiq; Amri, Rahyul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Early warning system is one of the technology to detect land fires by utilizing wireless sensor network. Continuously delivery of data by the sensor node causes a large energy consumption on the side of the node that can reduce battery life. This study was conducted to determine the battery durability in a long time during a fire and when there is no fire on peatland. The design of a portable power supply management system in the early warning system nodes is now used as a solution to get more energy efficiently and easy to operate. Power consumption savings on peatland fire detection systems using LM35 temperature sensor, Atmega8 microcontroller and HC-12 transmitter module. The results show that the best sleep mode feature on ATmega8 is in powerdown mode with a current of 0.287 mA. The range of distance that can be received by the transmitter module is 87 meters far without any obstacles. By using the time interval sleep / wake up scheduling at the time of data transmission able to minimize the large energy consumption and make long the active life of power supply with life time for 318 days..Keywords: ATmega8, Early Waring System, Power Supply, Sleep-wake up Scheduling.